The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1540-6229.12225
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Going Green in the Hotel Industry: Evidence from Beijing

Abstract: Based on several unique datasets in Beijing, this article investigates the value of going green in the hotel industry by combining the traditional hedonic pricing model with the state‐of‐the‐art content analysis of online reviews. The results indicate that the rate of complaints about the indoor environmental quality of green hotels is roughly 19% lower than that for nongreen hotels. Hedonic regression analysis concludes that green hotels enjoy a significant room rate premium of 6.5% without reducing occupancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 62 publications
0
14
0
13
Order By: Relevance
“…Zhang et al . () found a significant rate premium for green hotels in Beijing certified by the China National Tourism Administration under their Evaluation Standard for Green Hotels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al . () found a significant rate premium for green hotels in Beijing certified by the China National Tourism Administration under their Evaluation Standard for Green Hotels.…”
mentioning
confidence: 99%
“…There is no Energy Star certification program for whole multifamily buildings, only individual units. There are also Energy Star and LEED programs for hotels Zhang et al (2017). found a significant rate premium for green hotels in Beijing certified by the China National Tourism Administration under their Evaluation Standard for Green Hotels.9 As a robustness check, variables are winsorized at the 1st and 99th percentiles.…”
mentioning
confidence: 99%
“…Green office buildings have been found to receive a price premium of about 16 per cent in the United States (Eichholtz et al, 2010). Zhang et al (2020) found that green hotels can charge around 6.5 per cent more for rooms without a reduction in occupancy rates. Chegut et al (2020) analysed professional appraisals of rental housing, finding that energy efficiency has become important for valuations in more recent periods.…”
Section: Energy Effects On Real Estate Valuesmentioning
confidence: 99%
“…However, some hotel operators may think that environmental protection will harm their economic interests. Thus, companies do not voluntarily embrace standards that invite them to internalize environmental costs and risks (Zhang, Wu, Liu, & Zhang, 2017). In addition to the financial implications of customer experience and Green Practices, the lack of government legislation and enforcement also hampers the development of green hotels, enterprises are profit-oriented, lack government supervision, enterprises will not take the initiative to shoulder social responsibility (King, et al, 2017).…”
Section: Impact Of Policy In the Hotel Industry In Chinamentioning
confidence: 99%